2004
DOI: 10.1021/la049203h
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Thermosensitive Colloids Probed by Transmission Spectroscopy

Abstract: The kinetics of crystallization of poly-N-isopropylacrylamide (PNIPAM) particles has been investigated using the UV-visible transmission spectroscopy. Since the particle size decreases with the increase in temperature, microgel dispersions of different volume fractions have been obtained by varying the temperature of a single sample. It is found that the rates of the change in crystallinity, the average crystallite size, and the number density of crystallites at the most rapid stage over a certain time interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…Recent work has shown that thermosensitive suspensions are indeed excellent model systems for the study of colloidal crystals. 11,39,40 Then we demonstrate that flow curves up to effective volume fractions of 0.63 can be obtained. These data can then be used for a comparison with the theory of Fuchs and Cates, 37 and Fuchs.…”
Section: Gelsmentioning
confidence: 72%
“…Recent work has shown that thermosensitive suspensions are indeed excellent model systems for the study of colloidal crystals. 11,39,40 Then we demonstrate that flow curves up to effective volume fractions of 0.63 can be obtained. These data can then be used for a comparison with the theory of Fuchs and Cates, 37 and Fuchs.…”
Section: Gelsmentioning
confidence: 72%
“…(Scheme 1B)S ince the crystalline structure of microgel CCs is fragile and can be easily destroyed by heating or shearing, [22] it was first stabilized by forming ahydrogel matrix surrounding the microgel spheres, as shown in Scheme 1A. [23][24][25] As an example we synthesized aP NIPAM microgel CC doped with 10 %P (NIPAM-AAc) microgel.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, very fast density quenches and, furthermore, very high densities that require a compression or interpenetration of the particles can be studied. Moreover, a change from the compressed to the swollen state of the particles allows us to study the transition from HS-like to soft particles in a single experimental system [144,145]. With UV-visible spectroscopy measurements the crystallization kinetics of aqueous suspensions of PNIPAM particles was followed at different temperatures corresponding to volume fractions 0.51 < φ < 0.56 [145].…”
Section: Soft Particlesmentioning
confidence: 99%
“…Moreover, a change from the compressed to the swollen state of the particles allows us to study the transition from HS-like to soft particles in a single experimental system [144,145]. With UV-visible spectroscopy measurements the crystallization kinetics of aqueous suspensions of PNIPAM particles was followed at different temperatures corresponding to volume fractions 0.51 < φ < 0.56 [145]. In the swollen state, the kinetics of the crystallinity, the number of crystals and the average size of the crystals was found to be close to results obtained with HS in micro-gravity [64].…”
Section: Soft Particlesmentioning
confidence: 99%